2004
DOI: 10.1359/jbmr.040608
|View full text |Cite
|
Sign up to set email alerts
|

Residues Determining the Binding Specificity of Uncompetitive Inhibitors to Tissue-Nonspecific Alkaline Phosphatase

Abstract: Recent data have pointed to TNALP as a therapeutic target for soft-tissue ossification abnormalities. Here, we used mutagenesis, kinetic analysis, and computer modeling to identify the residues important for the binding of known ALP inhibitors to the TNALP active site. These data will enable drug design efforts aimed at developing improved specific TNALP inhibitors for therapeutic use. Introduction:We have shown previously that the genetic ablation of tissue-nonspecific alkaline phosphatase (TNALP) function le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 47 publications
(59 reference statements)
4
88
0
6
Order By: Relevance
“…Hydrolysis of pyrophosphate to inorganic phosphate by ALP underlies the mineralization of chondrocytes. [34][35][36] Our data suggest that CS and HA regulate the differentiation, i.e., mineralization of chondrocytes via direct suppression of ALP activity. Such control cells with ITS were confirmed to be AB-positive and some cartilage differentiation gene markers (Sox9, Runx2, Col2 and Aggrecan) of the cell were enhanced at this stage (data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…Hydrolysis of pyrophosphate to inorganic phosphate by ALP underlies the mineralization of chondrocytes. [34][35][36] Our data suggest that CS and HA regulate the differentiation, i.e., mineralization of chondrocytes via direct suppression of ALP activity. Such control cells with ITS were confirmed to be AB-positive and some cartilage differentiation gene markers (Sox9, Runx2, Col2 and Aggrecan) of the cell were enhanced at this stage (data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have shown that the initial step in serum-induced apatite formation is highly dependent on the concentration of calcium and phosphate in solution, and will not continue to occur when the calcium phosphate ion product falls below about 2.5 mM 3 (1, 2). (26)) and levamisole (an uncompetitive inhibitor (27,28)) completely prevented the uptake of serum calcium by bone, and Table 1 shows that bone samples incubated in serum with either beryllium or levamisole had no detectable calcium or phosphate, and did not stain with Alizarin red.…”
Section: Resultsmentioning
confidence: 99%
“…A unique feature of the active site of the mammalian enzyme in comparison to EcAP is the presence of Y367 at a distance of 6.1 Å to the phosphate ion. This tyrosine, which protrudes from the neighboring subunit into the active site, has been shown to be involved in the uncompetitive inhibition of mammalian APs [532,593]. To characterize the structural basis of the allosteric behavior and uncompetitive inhibition of PLAP, co-crystal structures with various ligands influencing the catalytic activity of the enzyme have been determined [594].…”
Section: Phylogenetic Relationshipmentioning
confidence: 99%